Predictors of Work Engagement: Leadership, Job Crafting and Restoration - Mariana Martins Pedersoli; Emmanuel Gonçalves e Silva; Elaine Rabelo Neiva (Paidéia (Ribeirão Preto))
Abstract: The job demands-resources model comprises the demands and resources that the job offers the employee. This study focuses on job demands and resources in the context of organizational change, in view of the employees’ work engagement in this context of change. Its objective was to test a model to see whether leader behavior, restoration and job crafting predict engagement, as well as to verify restoration mediation. A total of 251 employees took part. Change Leader Behavior Inventory, Job crafting, Restoration Experiences Scale, and Engagement - UWES instruments were used. Descriptive data analysis and structural equation modeling were performed. The results indicate a prediction between leader behavior and job crafting for work engagement and that restoration mediated the relationship between leader behavior and engagement. Thus, the research makes contributions to the issues involved, especially to work engagement in the context of organizational change.